Comparative Study of E?cacy of 0.5% Ropivacaine and 0.25% Levobupivacaine When Used in Tranversus Abdominus Plane Block for Post-Operative Analgesia in Lower Abdominal Surgeries - H. Baby Rani; Snigdha Reddy Patlolla (Academia Anesthesiologica International, 2021)
Background: Transversus Abdominis Plane Block (TAPB) is a form of regional anesthetic. After lower abdominal surgery, analgesia is provided, particularly if parietal wall pain is a major source of discomfort. The skin of the lower abdominal wall and the muscles above the Transversus Abdominis muscle can be visually blocked with local anesthetic deposition. The aim is to analysis was to see how effective 0.25 percent Levobupivacaine and 0.5 percent Ropivacaine is as an analgesic in the Transversus Abdominis Plane Block for Post-Surgical Analgesia following lower abdominal surgery. Subjects and Methods: The research included 60 patients between the ages of 18 and 60 who performed elective lower abdominal surgery and had an ASA score of I or II. Using an 18 gauge Tuohy needle and the double pop technique, the TAP block was developed. For a VAS greater than 4, rescue analgesia was administered postoperatively. Injection Tramadol was the pain reliever of choice. Rescue analgesia criteria were also reviewed. Results: In the demographic data, both categories were equal. In both classes, the diagnosis and the operations are undertaken were identical. In both classes, the decrease in the VAS score was equivalent. (P> 0.05). In both classes, the need for rescue analgesia in the postoperative phase was similar. Conclusion: Levobupivacaine and Ropivacaine have similar analgesia after lower abdominal surgery in the Transversus Abdominis Plane Block for Post-Surgical Analgesia.